Exploring the Role of Notaries in Common Law and Civil Law Legal Systems: A Comparative Analysis of Authentic Deed Making - Indi Nuroini; Akfah Zakiah Jamilah; Agung Wildan Azizi; Ajeung Syilva Syara Noor Silmi Sudrajat (PT. Anagata Sembagi Education, 2024)
The role of notaries in Civil Law and Common Law legal systems, with a focus on Indonesia and Malaysia as examples of each. The Civil Law legal system in Indonesia regulates notaries as public officials responsible for making authentic deeds with strong evidentiary power in the eyes of the law. This study uses a normative research approach to explore the legal regulations governing notaries in both legal systems, by analyzing the UUJN in Indonesia and the Notaries Public Act 1959 in Malaysia. The main findings show that notaries in Civil Law have broader authority in making authentic deeds compared to Notary Public in Common Law, which focuses more on document verification and attestation. This difference reflects the characteristics of each legal system in regulating the role of notaries in maintaining legal certainty in society. Further research on these differences and similarities can provide valuable insights for legal development in both systems, as well as help formulate more effective strategies in meeting the increasingly complex and connected global legal needs.